AB0640 Does mixed connective tissue disease without anti-u1rnp exist?. (15th June 2017) - Martínez-Barrio, J; Estrada, E; Ovalles-Bonilla, JG; Valor, L; Hernández-Flόrez, D; del, T Río; Janta, I; Gonzalez, JC Nieto; Serrano, B; González, R Benítez; Tenorio, C Sáenz; García-Montoya, L; et al.
Abstract : Background: Mixed Connective Tissue Disease (MCTD) is a systemic autoimmune rheumatic disease (SARD) characterized by clinical manifestations of systemic lupus erythematosus (SLE), systemic sclerosis (SSc) and polymyositis (PM) and the presence of anti-U1-RNP antibodies. Objectives: To determine whether there are patients with symptoms of MCTD in the absence of anti-U1-RNP antibodies. Methods: This was a monocentric, prospective, observational study of patients with SARD. All patients diagnosed of MCTD according to Kasukawa and/or Alarcόn-Segovia's criteria, SLE, SSc, PM, overlap syndromes (simultaneous or sequential criteria of 2 or more SARD), Sjögren's syndrome, Antiphospholipid syndrome, systemic vasculitis and undifferentiated or incomplete SARD (at least one clinical criterion of the classification criteria and a related antibody of any of the SARD) were included in the "Autoimmune Systemic Rheumatic Diseases Registry" of the Hospital General Universitario Gregorio Marañon Rheumatology Department from 1986 to 2012. The registry includes 2406 patients diagnosed with SARD. Patients with rheumatoid arthritis were excluded. Patients with clinical MCTD criteria were divided into seropositive (MCTD, with anti-U1RNP) and seronegative (possible MCTD, without anti-U1RNP). The registry counts with the local Institutional Ethics Board approval. Results: A total of 692 patients were recruited, 608 women (87.9%). Seventy (70, 10.1%) patients were classified as seropositive and 75 (10.8%) as seronegative by Kasukawa's criteria. Sixty-two (62, 8.9%) patients were classified as seropositive and 54 (7.8%) as seronegative according to Alarcόn-Segovia's criteria. There were no significant differences in age at disease onset, age at diagnosis or disease duration (p>0.05) between seropositive and seronegative patients. Seropositive patients with Kasukawa's criteria presented more frequently: lymphadenopathy, malar rash, leukopenia, Raynaud's phenomenon, muscle weakness and increase of muscle enzymes (Table 1 ). By Alarcόn-Segovia's criteria, patients who developed myositis were more frequent in the seropositive group (p=0.007, OR 3.25, 95% CI, 1.44–7.32). Conclusions: Some patients with SARD manifestations fulfill MCTD clinical criteria, both Kasukawa's and Alarcόn-Segovia's, in the absence of anti-U1-RNP antibodies from the onset of the disease and throughout its evolution (seronegative MCTD). The frequency of seronegative MCTD was similar to the frequency of seropositive MCTD. Patients with seropositive MCTD presented more frequently manifestations of SLE (lymphadenopathy, malar rash and leukopenia) when using Kasukawa's criteria and of PM when using both criteria. Disclosure of Interest: None declared